Penerapan Algoritma Additive Code Dalam Mengkompresi Record Database - Fauzan, Fathul (Jurnal Sains dan Teknologi Informasi, 2024)
The problem of storage space requirements in compressed record database applications is one of the main problems that can affect the performance of the compressed record database application itself. This is due to the large number of data records stored in the database. One solution that can be done to overcome this problem is to compress the database file. The compression process in this study was carried out based on the Additive Code algorithm by building a desktop-based database record compression application. The initial process carried out to implement this method is to prepare the SQL file to be compressed, the compression process takes place when the SQL file has finished uploading, then pressing the compression button on the database record compression application and the decompression process takes place when downloading the compressed SQL file and pressing the decompress button. on database record compression applications. Based on the results of the tests carried out, it was obtained that the Ratio of Compression (RC) was 1.33, the Compression Ratio (Cr) was reduced by 75%, Redundancy (Rd) was reduced by 25% and Space Saving (Ss) was reduced by 25%. These results indicate that the storage space requirements for database compression applications record databases more optimally than before the compression process was applied